Film and the Apologetics of Biblical Violence - Avalos, Hector (The journal of religion and film, 2009)
Most films that depict biblical violence are part of a broader apologetic effort to justify violence by biblical protagonists. In order to understand the variety and complexity of these apologetic efforts, the author introduces a typology that consists of five logical techniques that can be applied to biblical stories depicted on film: 1) deletion of violence; 2) addition of violence; 3) minimization of existing violence; 4) maximization of existing violence; 5) reconfiguration of violence. The author focuses on specific episodes in Jesus films and in films dealing with the life of Moses to illustrate his thesis.